Problems and Solutions for Teachers in Implementing the Independent Curriculum in the Society 5.0 Era - Sain, Shahzadi Hina; Ari, Ari Susetiyo; Hidayah, Iin Nur; Chusna, Fitri Nihayatul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Education is the cornerstone for building the future of a nation. The Indonesian government has implemented the Merdeka Curriculum as part of its transformation toward a Society 5.0 society in an effort to advance the education system. Although this initiative was intended to improve the quality of education, many issues have arisen during its implementation, particularly regarding the role of teachers as facilitators in the classroom. This article discusses the challenges faced by teachers when implementing the Merdeka Curriculum in the Society 5.0 era at SD NU Darusaalam Semen. By understanding these challenges, we hope to find better ways to improve the efficiency and equity of curriculum implementation. This will be a crucial step toward cultivating outstanding future generations. This study employs a qualitative descriptive approach. Qualitative research methods, based on post-positivist philosophy, were used to study the subject in its natural state, or real state, without experimental settings or conditions, with the researcher as the primary tool. The research findings indicate that the implementation of the Merdeka Curriculum at SD NU Darussalam Semen Kediri currently relies on student textbooks and curriculum guidelines as the primary implementation guidelines for teachers. In its implementation, there are several obstacles encountered in the implementation of the independent curriculum, where these obstacles are the same as the causes of teachers' lack of readiness in facing the independent curriculum. These obstacles include insufficient socialization about the implementation of the independent curriculum, insufficient activity of the Teacher Working Group (KKG), insufficient time for teachers to learn the independent curriculum due to being busy with class/school administration, and insufficient learning media for teachers. Challenges for teachers in implementing the independent curriculum include: teachers must be more creative, innovative, and able to assess students during the process, not just based on final grades. Additionally, students' challenges in understanding the independent curriculum include weak numeracy and literacy skills, as well as a lack of adequate learning materials. Solutions to these issues require collaboration among various parties, particularly the government as the policy-maker, by providing training for teachers and fostering the implementation of the Merdeka Curriculum to align with its focus and objectives. Additionally, participating in internal and external workshops, expanding knowledge about teaching methods, sharing with fellow educators, and changing mindsets are essential. Educators must be more active, creative, and innovative in delivering content to students, enhancing students' literacy and numeracy skills, teachers must allocate time to learn more about creating modules for the Merdeka Curriculum, and schools must ensure adequate facilities and infrastructure are in place.